Physical and chemical properties of an oxisol after maize cropping on rotation with leguminous plants - Danielle Medina Rosa (Bioscience Journal, 2019)
Crop rotation has been a daily management to ensure viability of no-tillage system; however, it is few accepted and practiced by farmers. Thus, this study aims to establish a crop rotation scheme in soil quality. Consequently, cover crops of dwarf mucuna, pigeon pea dwarf, sun hemp and maize were cropped in 2010 under no-tillage system. Soil properties were determined prior their beginning, after the management of cover crops and maize harvest. Results were submitted to ANOVA and averages were compared. The macroporosity and total porosity answered to the adopted management with some variation. So, cover crops need much time to express their potential, mainly related to the physical characteristics of the studied soil. Chemical properties are susceptible to this management since higher changes were observed after management with cover crops. This crop rotation in a long term may allow the maintenance of soil quality because it avoids losses of nutrients and carbon.